Crystallization and preliminary X‐ray crystallographic analysis of the CARD domain of apoptosis repressor with CARD (ARC). Issue 1 (1st January 2015) - Kim, Seong Hyun; Park, Hyun Ho
<x xml:space="preserve">Abstract</x> Apoptosis repressor with caspase‐recruiting domain (ARC) is an apoptosis repressor that inhibits both intrinsic and extrinsic apoptosis signalling. Human ARC contains an N‐terminal caspase‐recruiting domain (CARD domain) and a C‐terminal proline‐ and glutamic acid‐rich (P/E‐rich) domain. The CARD domain in ARC is the domain that is directly involved in inhibition of the extrinsic pathway. In this study, the N‐terminal CARD domain of ARC was overexpressed, purified and crystallized. X‐ray diffraction data were collected to a resolution of 2.1 Å and the crystals were found to belong to space group P61 or P65, with unit‐cell parameters a = 98.28, b = 98.28, c = 51.86 Å, α = 90, β = 90, γ = 120°.